2011
DOI: 10.1519/jsc.0b013e3181c64308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Running Velocity on Running Kinetics and Kinematics

Abstract: View the peer-reviewed version (peerj.com/articles/3298), which is the preferred citable publication unless you specifically need to cite this preprint. Fukuchi RK, Fukuchi CA, Duarte M. (2017) A public dataset of running biomechanics and the effects of running speed on lower extremity kinematics and kinetics. PeerJ 5:e3298 https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
77
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 23 publications
23
77
1
3
Order By: Relevance
“…were in good overall agreement with previous studies [23][24][25][26][27]. Furthermore, the difference in these variables between Clusters 1 and 3 were in agreement with studies comparing MFS / FFS and RFS runners [5,9].…”
Section: Resultssupporting
confidence: 91%
“…were in good overall agreement with previous studies [23][24][25][26][27]. Furthermore, the difference in these variables between Clusters 1 and 3 were in agreement with studies comparing MFS / FFS and RFS runners [5,9].…”
Section: Resultssupporting
confidence: 91%
“…Recent research has shown high levels of horizontal force application is related to faster sprinting speeds. [11][12][13][14][15] Contreras and colleagues 16 found that the hip thrust is effective for improving both horizontal jump distance and sprinting performance.…”
Section: Introductionmentioning
confidence: 99%
“…[23] and resisted sprinting [28] whereby velocity and stride length increase and joint range of motion may decrease with increased distance.…”
Section: Discussionmentioning
confidence: 99%